Legal Basis for Deciding Cases of Criminal Acts of Sexual Violence against Minors - Hariyanto, Hariyanto; Rokhim, Abdul; Isnaeni, Diyan (JURNAL MERCATORIA, 2024)
This research aims to describe the legal basis for deciding cases of criminal acts of sexual violence against minors. This research uses normative legal research methods. Normative legal research methods are used to analyze and evaluate statutory regulations, legal documents, and other legal literature. This method aims to understand, interpret, and provide insight into applicable legal norms. The research results show that the legal basis for deciding cases of criminal acts of sexual violence against minors is as follows: 1) Law Number 35 of 2014 concerning Child Protection; 2) Law Number 23 of 2002 concerning Child Protection; 3) Law Number 17 of 2016 concerning the Determination of Government Regulations in place of Law Number 2 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection into Law; 4) Law Number 11 of 2012 concerning the Juvenile Criminal Justice System; 5) Law Number 21 of 2007 concerning Eradication of the Crime of Human Trafficking. Apart from this law, there are also government regulations, regional regulations, and other regulations which also regulate child protection and sexual violence against minors in Indonesia.